Research of methods for constructing ecosystem models of educational software - Жигаревич, Оксана Костянтинівна (Technology audit and production reserves, 2015)
In this paper a clear definition is given for ecosystems of the software and an ecosystem model is also constructed with ecosystem concept of educational software is also reviewed and studied here. The algebra systems using with presenting the educational software ecosystem are taken with the got results of algebraic operations conjunction over the autonomous component systems. The ecosystem models of educational software are presented: using Petri network, the case of the ecosystem diagrams using and SR ecosystem models. The UML model of the educational software ecosystem is investigated, that can be represented using use-case diagrams. An analytical view of educational software through using Petri nets is also presented in the article. It is considered that the ecosystem of educational software is presenting an association of the software developers, software users, and relevant educational institution. It needs to understand that the key role in this interaction plays a human, because in case that he/she develops, uses and learns it. It can be possible talk about the ecosystem of educational software as one of the science branches that has to be explored a long time.